Inspection on Railroads Quality by using Image Processing Method - Budiono Budiono; Suwarsono Suwarsono (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2019)
The condition of railroads is the main determinant of train safety. The recent railroads inspection conducted by the mechanic results inaccurate inspection and it cannot be conducted continuously. Therefore, this research develops the inspection by using Image Processing Method. Image processing facilitates and accelerates the measurement of railroads quality. This technique enables the automation of railroads measurement in continuous and faster process. It is as the inspection needs no direct measurement. The image processing conducted in this research uses edge detection method with filter disk 12. For collecting data, this research uses laser line and camera to capture figure of the railroads. Furthermore, the figure data is analyzed by using Matlab software. Output of image processing is graphic of the railroads surface that is analyzed to obtain its quality from its flatness. Result of railroads surface measurement by using image processing is averagely 3.61311 mm height and 55.6000 mm width. It is validated with manual measurement by the result of average height is 3.63 mm and average width is 5.5385 mm. The normal flatness of railroads by using image processing is 0.4488 mm. Inspection by using image processing is feasible as the alternative for substituting the manual process previously conducted.